2012
DOI: 10.1590/s0103-21002012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Sinvastatina e lesão renal aguda isquêmica em ratos

Abstract: Objectives:The study aimed to verify the protective renal action of simvastatin in an animal model of ischemia / reperfusion for 30 minutes. Methods: Ischemia was obtained by clamping bilateral renal pedicles for 30 minutes, followed by reperfusion. Male Wistar rats were used, weighing between 250-300g, distributed into the following groups: SHAM (control, without clamping renal), Ischemia (renal ischemia for 30 minutes), Ischemia + Statin (simvastatin 0.5 mg/kg, orally for three days). Renal function (creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
3
Order By: Relevance
“…Iseri et al (14) showed that treatment with simvastatin-ameliorated nephrotoxicity and reversed renal function by increasing the level of antioxidant enzymes. Teshima et al (34) demonstrated that statin treatment revealed decreased ROS and subsequent improvement in renal function in an in vivo ischemic AKI model.…”
Section: Discussionmentioning
confidence: 99%
“…Iseri et al (14) showed that treatment with simvastatin-ameliorated nephrotoxicity and reversed renal function by increasing the level of antioxidant enzymes. Teshima et al (34) demonstrated that statin treatment revealed decreased ROS and subsequent improvement in renal function in an in vivo ischemic AKI model.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental studies confirm these results, since the administration of simvastatin in a cisplatin-induced nephrotoxicity model resulted in improved renal function, with an increase in the level of antioxidant enzymes and reduction of oxidative metabolites (24) . An in vivo study in ischemic AKI model associated with statin therapy showed a reduction of ROS and consequent improvement in renal function (14) .…”
Section: Rev Esc Enfermmentioning
confidence: 96%
“…at the end of the CPL (cecal puncture ligation) procedure in the sixth, eighth, and 24th hours of the postoperative period (13) ; SHAM + Statin -the animals were preconditioned with 0.5 mg/kg of simvastatin by gavage (p.o.) for five days, once a day (14) and underwent laparotomy (cecal manipulation), with start of fluid resuscitation; Sepsis -the animals were anesthetized with ketamine / xylazine (75 mg/kg / 10mg/kg) intraperitoneally and underwent laparotomy for completing the CPL procedure with fluid resuscitation; Sepsis + Statin -the animals were pretreated with simvastatin for five days and submitted to CPL and fluid resuscitation.…”
Section: Animalsmentioning
confidence: 99%
“…Os animais dos grupos Estatina, foram pré-condicionados com 0,5 mg/kg de sinvastatina (Sinvascor®, Baldacci), por gavagem (vo), durante cinco dias, uma vez ao dia (37,38) .…”
Section: Administração De Estatinaunclassified
“…Ainda, em outro modelo de nefrotoxicidade induzida pelo contraste iodado, a administração sinvastatina confirmou aumento da taxa de enzimas antioxidantes e redução de mediadores oxidativos, como o NO (24) . Em estudo in vivo com o modelo de LRA isquêmica associado ao tratamento com estatinas, realizado nesse laboratório -LEMA, observou-se resultados semelhantes, com redução de espécies oxidantes como os H 2 O 2 e o MDA e consequente melhora da função renal (37,38) .…”
Section: I S C U S S ã O | 47unclassified